PEMANFAATAN INSTAGRAM LEMBAGA LAYANAN PENDIDIKAN TINGGI (LLDIKTI) WILAYAH II SEBAGAI MEDIA INFORMASI TENTANG PERGURUAN TINGGI - Nur Khairun Niswah; Dwi Maharani (Journal of Innovation Research and Knowledge, 2025)
This study is titled "The Utilization of Instagram by the Higher Education Service Institution (LLDIKTI) Region II as an Information Medium about Higher Education." The aim of this research is to identify how LLDIKTI Region II utilizes Instagram as a medium for disseminating information about higher education. The research employs a qualitative approach with a descriptive qualitative method. Data were collected using three main techniques: in-depth interviews, observation, and documentation. These three techniques were applied simultaneously to obtain comprehensive and relevant data in line with the research focus. The theories used in this study are the New Media Theory, Uses and Gratification Theory, and Media Richness Theory. The findings indicate that Instagram has become an effective medium for LLDIKTI Region II to deliver higher education information quickly, widely, and visually. The utilization of various features such as feed, stories, reels, and highlights enables the institution to reach audiences with diverse preferences, aligning with the theories applied.